Transform of Artificial Immune System algorithm optimization based on mathematical test function - Yaw M.W.; Chong K.H.; Kamil K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Control systems; Functions; Gallium; Genetic algorithms; Immune system; Mathematical transformations; Artificial Immune System; Artificial immune system algorithms; Biological immune system; Complex optimization problems; Global searching; Hybrid algorithms; Hyper mutation; Test functions; Optimization